Assessment of anthropometric indices in patients with phenylketonuria - Shakiba, Marjan; Alaei, Mohammadreza; Saneifard, Hedyeh; Mosallanejad, Asieh (Iranian Journal of Child Neurology, 2020)
Background: Dietary phenylalanine restriction is the main treatment of phenylketonuria (PKU, OMIM 261600). There are studies which have demonstrated growth retardation in these patients, and some are in contrast. This study is done to assess the growth parameters of treated PKU patients. Method : 105 treated PKU patients were compared to 105 controls matched in age, sex and birth weight. Weight, height, head circumference, weight for height and BMI (weight/height2) were measured and transformed into Z-scores. Correlations between pretreatment plasma Phenylalanine concentrations mean plasma Phenylalanine concentrations, and anthropometric parameters were analyzed in patients. Findings: There was no significant difference between weight Z-scores, weight/height and BMI means, in patients and controls (P: 0.842, p: 0.257, p: 0.622 respectively). There was a significant decrease in height Z-scores of patients more than 2 years old (P: 0.005). Also, there was a significant decrease in patient’s Head circumference than controls’(P: 0.03), however this significance got more in patients above 3 years old (P: 0.001). There was not a significant correlation between weight and height Z-scores, and patients’ pretreatment plasma phenylalanine (P: 0.054 and 0.15), however this correlation was positively significant in HC Z-scores (r= -0.445, P: 0.01).Moreover,no correlation was found between growth parameters and mean plasma phenylalanine concentrations. Conclusions: Growth parameters are not impaired in early treated PKU patients; however height in patients more than 2 years old and Head circumference in patients more than 3 years old were retarded. Disease severity is a more effective factor in HC growth than dietary adherence.